The Impact of Managerial and Principal Academic Supervision on Teacher Performance - Anis Zohriah; Anis Fauzi; Intan Rahman Pandini (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Supervision is carried out in the context of mentoring, directing, and coaching toward improving teacher performance more optimally. This study aims to determine how managerial and principal academic supervision affect teacher performance in private junior high schools in the Tigaraksa District of the Tangerang Regency. This study uses correlational and regression analysis, which are both types of quantitative research methods. The population comprises 41 teachers, three principals, and one supervisor, for a total of 45 respondents. This study takes a sample of the whole population, which is the whole population. With a 97% contribution, the results showed that managerial supervision greatly improved teacher performance. The study's development shows that the principal's academic control has a significant effect on improving teacher performance, with a contribution of 88%, and that the supervisor's managerial supervision and the principal's visionary leadership have a substantial impact on improving teacher performance, with a contribution of 91%.